70-20-10 and the Dominance of Informal Learning: A Fact in Search of Evidence. (June 2018) - Clardy, Alan
It is now widely accepted that informal learning plays a critical role in all workplace learning. Five different literature traditions examined here seemingly converge on the claim that 70% or more of work-based learning occurs informally. Referred to here as the 70% rule, that rule is now seen as a basic fact in the field. Yet a detailed examination of this literature finds that the evidential basis for the 70% rule is weak; human resource development (HRD) policies relying upon that claim are likely to be misleading. The research and scholarship cited in these traditions are critiqued in terms of sloppy scholarship, inconsistent conceptualizations, and fundamental research protocol problems. The implications from this review suggest that the 70% rule of informal learning needs to be set aside. The conclusions to this research offer propositions for redefining the focus of formal and informal work-based learning along with revising the role of HRD in organizations.